Kajian strategi pengiklanan Bandar Raya peranginan Miri - Martina, Anak Gani. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The research is done on the campaign and promotional strategy to promote Miri Resort City. Hence, creating a campaign to promote Miri resort City locally and internationally. The used of creative graphic elements with real photo could helps to boost the image and identity of Miri as a resort City.